Measurements of the Rayleigh wave propagation velocity n the polymer layers - KRZEŚNIAK, Zenobia; RANACHOWSKI, Jerzy; RZESZOTARSKA, Jadwiga; JAKUBCZYK, Zdzisław (Archives of Acoustics, 1987)
In the paper are presented the results of measurements of the Rayleigh wave propagation velocity in the polyvinyl carbazole (PCV), polyvinyl carbazole with trinitro-fluorenon (PVC-TNF) and their halogen derivatives. The correlation relationship between the activation energy of the investigated compounds and the linear combination of the squares of longitudinal and transverse ultrasonic wave velocity was found to be linear.